HUBUNGAN ANTARA TINGKAT DAN INTENSITAS SERANGAN HAMA PENGGEREK BUAH KAKAO (conopomorpha cramerella) TERHADAP PRODUKSI KAKAO DI KECAMATAN MANYAK PAYED - Sara, Fatia; Mulyani, Cut; Iswahyudi, Iswahyudi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
The purpose of this study was to determine the effect of cocoa pod borer (CPB) pest attack intensity on cocoa production in Manyak Payed District. This study used a survey method, sampling was carried out using a "purposive" method which was carried out in 3 villages, namely Lhueng Manyoe village, Krueng Sikajang village, Pahlawan village starting from August to September 2022. In each of the observed garden criteria, percentage and The intensity of CPB pest attacks shows different levels because of the way cocoa farmers tend their farms so that there are plantations that have the highest CPB pest attack rates and there are gardens that have the lowest CPB pest attack rates. The gardens with the highest attack rate were found in the village of Lhueng Manyoe with the category of unkempt gardens and the lowest attack was found in the village of Krueng Sikajang with the category of conventionally treated gardens. The average attack intensity on all observed plantations was 24%. Meanwhile, the loss of cocoa yield reached 275.96 kg/ha/year.